OC-012 Do inflammatory polyps show features associated with the early stages of malignant progression?. (22nd June 2015) - Jawad, N; Johnson, C; Butterworth, E; Saeed, I; Feakins, R; Rodriguez-Justo, M; McDonald, S; Wright, N; Silver, A
Abstract : Introduction: Inflammatory polyps (IP) are associated with chronic idiopathic inflammatory bowel disease (IBD). Colonoscopic surveillance programmes do not always consider IP to be important and their presence is recorded incompletely. Here, IPs were assessed for features of malignant change. The aims were to: assess the spatial and temporal relationship between IP and pre-malignant and malignant lesions; examine proliferation rates and stem cell compartment expansion of IP crypts; and compare microRNA (miRNA) profiles in inflammation, dysplasia and IP. Method: A retrospective case-control observational study of IBD patients from Bart's Health NHS Trust, Queens University, University College London and The Homerton University Hospitals assessed the spatial and temporal relationship between IP and lesions. IP crypts (n = 30) with matched normal tissue were analysed for proliferation rates and stem cell compartment expansion using immunohistochemistry (Ki67) and in situ hybridisation (LGR5). MicroRNAs (miRNAs) profiles for inflammation, dysplasia and IP were determined using NanoString nCounter Analysis. Results: Sporadic adenoma (n = 41) was significantly associated with IP (38/41; p < 0.0001). In 21% (12/58) of cases, pre-malignant lesions (sporadic adenoma, hyperplastic polyp, flat dyplasia and dysplasia associated lymphoid mass) or carcinoma developed at a recorded IP site. In 38% of cases (5/13), cancer developed in a previous IP site. The Ki67 proliferation index was significantly higher in IP (p < 0.005) than controls (29.2% vs. 23%). There was a limited increase in LGR5 + stem cell numbers in IP crypts. Thirty-six differentially expressed miRNAs were identified in three groups (IBD-IP; IBD-dysplasia; IBD-inactive/active (adjusted p-value <0.05). Fourteen miRNAs were upregulated in IBD-IP compared to IBD and IBD-dysplasia including miR-493, miR-29a and miR-29c all involved in cancer and/or IBD. Conclusion: IP have characteristics typical of malignant progression: increased cellular proliferation and possibly limited expansion of the stem cell compartment. Microarray profiles can distinguish IBD mucosa from dysplasia and IP. Combined with our previous observation of somatic mutations in IP, these findings suggest IPs are not benign entities and may be associated with increased risk of neoplasia. IPs require investigation to identify biomarkers for stratification of cancer risk in IBD patients. Disclosure of interest: None Declared.